Marjolin’s ulcer in chronic wounds – review of available literature - Dariusz Bazaliński; Joanna Przybek-Mita; Beata Barańska; Paweł Więch (Contemporary Oncology, 2017)
Marjolin’s ulcer is a rare, aggressive skin cancer developing in scar tissue, chronic ulcers and areas affected by inflammations. Its incidence is estimated to range from 1% to 2% of all burn scars. It most frequently takes the form of squamous cell carcinoma which sometimes is diagnosed during examination of lesions developing in scars and hard-to-heal chronic wounds (pressure sores, leg ulcers). Therapeutic management of Marjolin’s ulcer requires well-designed treatment plan to ensure optimal medical care and good quality of life for the patient. The high risk of metastases and damage to the structure of vitally important organs determines the need for early diagnosis and prompt surgical intervention with supplementary therapy. The purpose of the study was to examine etiopathogenesis of Marjolin’s ulcer and principles of its treatment. The authors focused on the aspect of malignant degeneration in chronic wounds (leg ulcers, pressure sores) as a very rare, aggressive form of Marjolin’s ulcer. A review of the available literature on the issue of Marjolin ulcers was conducted using the key words; Marjolin ulcers, pressure sore, chronic wound. Malignant degeneration in chronic wounds is a very rare aggressive form of Marjolin ulcer. Increased oncological alertness should be displayed by nursing and medical personnel taking care of patients with chronic wounds.